Phosphoinositol 3-kinase-driven NET formation involves different isoforms and signaling partners depending on the stimulus - de Carvalho Oliveira, Vanessa; Tatsiy, Olga; McDonald, Patrick P. (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) can immobilize and kill pathogens, but also contribute to the progression of several inflammatory and auto-immune diseases, as well as cancer. Whence the importance of elucidating the mechanisms underlying NET formation. In this regard, the PI3K signaling pathway has been shown to be crucial; yet little is known about which of its components are involved. Here, we identified the PI3K isoforms and associated signaling partners that are mobilized in response to different classes of physiological NET inducers. Across the various stimuli used, PI3Kα and PI3Kγ isoforms clearly contributed to NET induction, while the participation of other isoforms was stimulus-dependent. Some PI3K isoforms were also found to signal through Akt, the canonical downstream effector of PI3K, while others did not. Downstream of PI3K, mTOR and PLCγ2 were used by all stimuli to control NET generation. Conversely, the involvement of other kinases depended on the stimulus – both TNFα and GM-CSF relied on PDK1 and Akt; and both TNFα and fMLP additionally used S6K. We further established that all PI3K isoforms and downstream effectors act belatedly in NET generation, as reported previously for PI3K. Finally, we revisited the PI3K-PDK1-Akt signaling hierarchy in human neutrophils and again found stimulus-dependent differences. Our data uncover unsuspected complexity and redundancy in the signaling machinery controlling NET formation through the all-important PI3K pathway. Conserved signaling molecules represent therapeutic targets for pathologies involving NETs and in this regard, the existence of drugs currently used in the clinic or undergoing clinical trials (which target PI3K isoforms, mTOR or Akt), underscores the translational potential of our findings.